KEEFEKTIFAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTU MEDIA AUGMENTED REALITY TERHADAP MINAT BELAJAR SISWA KELAS IV TEMA 6 SUBTEMA 1 DI SDN 3 TUBANAN - Charisma Annuritza Arliana; Fine Reffiane; Suyitno Suyitno (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
The background that drives this research is the low interest in student learning caused by a lack of innovation or variation in learning activities and not using technology-based learning media.The purpose of this study was to determine the effectiveness of the Problem Based Learning learning model assisted by Augmented Reality media on the learning interest of fourth grade students in Theme 6 Sub-theme 1 at SDN 3 Tubanan. This type of research is quantitative research in the form of Pre-Experimental Design with One Group Pretest-Posttest Design. The sample in this study was 20 students who were taken using a non-probability sampling technique with a saturated sampling type (census). Data collection methods were obtained through questionnaires and observations. Based on the results of data analysis, it is known that the average posttest score is higher than the average pretest score. The results of the t-test analysis obtained tcount of 10.273 and ttable of 2.093 with db = n-1 = 19 from the significance level = 0.05. Because tcount > ttable, then H0 is rejected and H1 is accepted. Thus, it can be concluded that the Problem Based Learning learning model assisted by Augmented Reality media is effectively used to increase interest in learning for fourth grade students, especially on theme 6 sub-theme 1.